Behaviour and biochemical responses of the marine clam Ruditapes decussatus exposed to phosphogypsum. Issue 23 (15th October 2021) - El Ayeb, Nesrine; Béjaoui, Mustapha; Muhr, Hervé; Touaylia, Samir; Mahmoudi, Ezzeddine
ABSTRACT: The phosphate fertilizer and phosphoric acid industries increase phosphogypsum levels in the aquatic environment leading to various disturbing effects. In the present work, we investigated the bio-uptake of heavy metals following the exposure of Ruditapes decussatus to three concentrations of phosphogypsum, 10, 20 and 40 g kg −1, under laboratory conditions. The amounts of Zn, Cd and Pb in several organs of the clam Ruditapes decussatus was determined using inductively coupled plasma optical emission spectroscopy (ICP-OES). Phosphogypsum acts on the behaviour of R. decussatus by increasing filtration rates. The most treatments showed significantly higher metal concentration in all tissues than the controls. Excavation behaviour was altered in treated bivalves compared to controls. The filtration rate (FR) of clams was significantly affected by exposure to phosphogypsum. Indeed, FR increased in clams exposed to phosphogypsum. Phosphogypsum has decreased SOD, CAT and MDA activities in the gills, digestive gland, gonad and muscles according to the concentration indicating a defense against oxidative stress. AChE was significantly inhibited in clams from all the sampling sites compared to controls. The considered parameters could be useful biomarkers for the evaluation of phosphogypsum toxicity in threatened biota. This study was conducted as part of a further investigation into the use of a comprehensive approach combining chemical and biological parameters to assess the health status of the Gabes gulf population. It provides the first database referring to phosphogypsum contamination and its biological effect in this ecosystem. The present study fills in a needed gap in the literature. GRAPHICAL ABSTRACT: UF0001